STATUTORY AND CORPORATE GOVERNANCE CONCERNS ON INVESTMENTS BY - Lekone, Barati; Mukuna, John (European Scientific Journal, ESJ, 2014)
This article explores the statutory underpinnings and corporate governance perspectives of investments by pension funds in Botswana. Specifically, the article evaluates the scope of the Non-Bank Financial Institutions Regulatory Authority Act (NBFIRA Act); Pension and Provident Funds Act (PPFA) and attendant delegated legislation in the context of investment considerations by pension funds. It examines the extent to which the country’s corporate governance terrain and laws regulating investments by pension funds embrace the concept of good corporate governance. The enquiry is motivated by the critical role played by effective corporate governance in a company’s corporate strategy, endeavour for longevity and its role as a good corporate citizen. Thus it becomes critical to investigate the legal framework and corporate governance perspectives of pension funds, a critical sector in the economy of Botswana. The article finds that the Botswana’s statutory infrastructure and corporate governance environment fail to create an effective platform which would incorporate and inculcate a culture of good corporate governance as pension funds deliberate on how to invest the billions of Pula entrusted to them as fiduciaries. Defaulting to adopt a cogent and forceful re-examination of the relevant law and good governance is disaster in waiting which the findings of this article strive to forestall.